Maternal-Fetal Medicine Workforce in the United States - Rayburn, William F.; Klagholz, Jeffrey C.; Elwell, Erika C.; Strunk, Albert L. (American Journal of Perinatology, 2012)
Objective To identify the current supply and locations of maternal-fetal medicine (MFM) subspecialists in active practice in the United States.Study Design This observational study examined the membership roster of the American Congress of Obstetricians and Gynecologists in 2010 for those whose practice was in either general obstetrics and gynecology or maternal-fetal medicine. Reliable national databases were used to determine the numbers and locations of births annually, reproductive-aged (15 to 44 years old) women, and level III perinatal centers in each state.Results There were 1355 MFM subspecialists in the United States in 2010 with the highest number being in the most populous states. Nearly all (98.2%) resided in metropolitan counties with level III perinatal center(s). Nationwide, there was one MFM subspecialist for every 24 general obstetrician-gynecologists and for every 3150 births. States with the highest number of MFM subspecialists per 10,000 live births were Vermont (9.5), Connecticut (6.4), Maryland (5.8), New Jersey (5.7), Hawaii (5.7), and Massachusetts (5.6). The lowest densities were in Indiana (1.5), Mississippi (1.3), Idaho (1.2), and Arkansas (1.0), and North Dakota and Wyoming had none.Conclusion Data from this population-level study will serve as a baseline to follow trends in the workforce of MFM practitioners.
Keywords: maternal-fetal medicine; workforce; subspecialists; distribution